Reliability of high-resolution ultrasonography in the assessment of Achilles tendon enthesopathy in seronegative spondyloarthropathies - DİRESKENELİ, RAFİ HANER (B M J PUBLISHING GROUP, 2009)
Objective: The present study was mainly aimed at investigating the interobserver and intraobserver reproducibility of ultrasound (US) results in the assessment of Achilles tendon enthesopathy in patients with seronegative spondyloarthropathies (SpA). Methods: A total of 28 patients with a diagnosis of SpA according to the European Spondyloarthropathy Study Group criteria were included. The patient female/male ratio was 1.8 (18/10), mean age was 42 (range 25-75) years and mean disease duration was 9 (range 1-35) years. Mean (SD) Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) scores were 32.4 (14.5) and 26.3 (9.2), respectively. Bilateral Achilles tendon US examinations were carried out independently by three investigators using a MyLab70 XVG (Esaote Biomedica, Genoa, Italy), equipped with a broadband 6-18 MHz linear probe. Each Achilles tendon was scanned for assessing the presence/absence of US findings indicative of enthesopathy according to the Outcome Measures in Rheumatoid Arthritis Clinical Trials (OMERACT) preliminary definition. The same findings were also scored on a 3-grade semiquantitative scoring system on which investigators reached a consensus prior to the study. Total additive scores per Achilles tendon were calculated. Results: Moderate to excellent interobserver and intraobserver agreements were found for most of the US findings indicative of enthesopathy. Similar results were obtained using semiquantitative assessments, with weighted kappa values estimating the interobserver and intraobserver agreements for soft tissue inflammation of 0.696 and 0.816, respectively and for tissue damage 0.711 and 0.901, respectively. Conclusion: US assessment of Achilles tendon enthesopathy in patients with SpA, using the OMERACT preliminary definition, was found to be reliable. Bone irregularity and entheseal hypoechogenicity were the most difficult abnormalities to reach agreement on.
Keywords: POWER DOPPLER US; MUSCULOSKELETAL ULTRASOUND; ANKYLOSING-SPONDYLITIS; INTEROBSERVER RELIABILITY; PERIPHERAL ENTHESITIS; LOWER-LIMB; RHEUMATOLOGY; CLASSIFICATION; SYNOVITIS; AGREEMENT